Reconstructing Homo Islamicus through Hifz al-Bi’ah: An ecological paradigm for contemporary Islamic economics - Mursal, Mursal; Hulwati, Hulwati; Rozalinda, Rozalinda; Fauzi, Muhammad; Nenengsih, Nenengsih (Journal of Islamic Economics Lariba, 2025)
IntroductionContemporary ecological crises have exposed the ethical and epistemological limitations of dominant economic paradigms that prioritize growth, utility maximization, and anthropocentric rationality. Within Islamic economics, the concept of Homo Islamicus has been advanced as an alternative model of economic agency grounded in moral, spiritual, and social values. However, despite Islam’s explicit prohibition of environmental destruction and its emphasis on stewardship, ecological responsibility has not been articulated explicitly or systematically within many conceptualizations of Homo Islamicus. This gap becomes increasingly significant as sustainability and environmental justice emerge as central global concerns.ObjectivesThis study aims to critically re-examine the conceptual construction of Homo Islamicus in Islamic economics literature and to assess the extent to which ecological ethics, particularly Hifz al-Bi’ah (environmental preservation), are integrated into this model. It seeks to identify conceptual gaps, evaluate the relevance of ecological ethics within Islamic economic agency, and propose a paradigmatic reconstruction that aligns Homo Islamicus with contemporary sustainability challenges.MethodThe study employs a qualitative literature analysis design based on a purposive selection of fifteen Scopus-indexed journal articles discussing Homo Islamicus and related concepts of Islamic economic agency. Using a modified analytical framework adapted from established qualitative synthesis methods, the analysis proceeds through three stages: identifying definitions of Homo Islamicus, tracing embedded ecological values and principles related to Hifz al-Bi’ah, and evaluating the role of ecological ethics within these conceptual frameworks.ResultsThe findings reveal that while Homo Islamicus is consistently portrayed as a morally guided and socially responsible agent, ecological responsibility remains largely implicit, symbolic, or secondary. Recent developments in maqāṣid al-sharīʿah, especially the discourse on Hifz al-Bi’ah, provide a strong normative basis for environmental ethics, yet this has not been fully integrated into models of economic agency.ImplicationsIntegrating Hifz al-Bi’ah into the core of Homo Islamicus strengthens Islamic economics as an ethical framework capable of addressing sustainability and ecological justice.Originality/NoveltyThis study offers a paradigmatic reconstruction of Homo Islamicus as an ethical–ecological economic agent, contributing to the advancement of Islamic economics as a transformative normative social science responsive to contemporary environmental challenges.